2009
DOI: 10.1521/jscp.2009.28.5.650
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement Motives Mediate the Positive Association Between Mind/Body Awareness and College Student Drinking

Abstract: This study was undertaken to examine the relationship between mindfulness and alcohol consumption among college students, with enhancement and coping motives evaluated as potential mediators. Differences between men and women in drinking and mindfulness (mind/body awareness specifically) were also considered. Undergraduate students (n = 212, 51% male) completed a survey that included measures of mindfulness, drinking motives, and drinking. Results indicated that greater mind/body awareness was associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
46
5

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 61 publications
3
46
5
Order By: Relevance
“…Enhancement motives are conceptually related to positive reinforcement, and can be described as drinking to enhance a pleasant feeling. Previous research consistently links enhancement motives with problematic drinking (e.g., Leigh & Neighbors, 2009; Palfai, Ralston, & Wright, 2011). Further, enhancement motives have unique relationships with college alcohol behaviors relative to other motives (e.g., Leigh & Neighbors, 2009).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Enhancement motives are conceptually related to positive reinforcement, and can be described as drinking to enhance a pleasant feeling. Previous research consistently links enhancement motives with problematic drinking (e.g., Leigh & Neighbors, 2009; Palfai, Ralston, & Wright, 2011). Further, enhancement motives have unique relationships with college alcohol behaviors relative to other motives (e.g., Leigh & Neighbors, 2009).…”
Section: Discussionmentioning
confidence: 90%
“…Previous research consistently links enhancement motives with problematic drinking (e.g., Leigh & Neighbors, 2009; Palfai, Ralston, & Wright, 2011). Further, enhancement motives have unique relationships with college alcohol behaviors relative to other motives (e.g., Leigh & Neighbors, 2009). This could explain why direct effects emerged for enhancement but not other motives, and indicates that intervention approaches highlighting non-alcohol-related methods for achieving enhanced pleasant feelings may have unique benefit.…”
Section: Discussionmentioning
confidence: 90%
“…Although there generally appears to be a negative relationship between trait mindfulness and substance use behaviors (Black et al, 2012; Bramm et al, 2013; Brewer et al, 2009; Brister, 2012; Rogojanski et al, 2011), some studies have failed to find this relationship (Phillip, 2010; Rendon, 2006) or have reported a positive relationship between trait mindfulness and substance use behaviors (Leigh and Neighbors, 2009; Leigh et al, 2005). …”
Section: Introductionmentioning
confidence: 99%
“…Mindfulness research also has been conducted with Caucasian college students. There is minimal research in the literature, however, on mindfulness in African-American college students and no information on mindfulness and alcohol use in this population (Leigh & Neighbors, 2009;Vernig & Orsillo, 2009). The present study possibly was the first to examine the relationship of mindfulness, alcohol use, and religion among African-American college students.…”
Section: Discussionmentioning
confidence: 99%
“…There is scant information, however, on mindfulness in African-American college students, and no research has been conducted on mindfulness and alcohol use in African-American college students (Leigh & Neighbors, 2009;Masuda, Anderson, & Sheehan, 2009;Masuda & Tully, 2012;Vernig & Orsillo, 2009). One possible explanation for lack of research in this area may be inaccessibility to the population by current mindfulness researchers.…”
mentioning
confidence: 99%